Monitoring Peri-Therapeutic Cerebral Circulation Time: A Feasibility Study Using Color-Coded Quantitative DSA in Patients with Steno-Occlusive Arterial Disease - Lin, C.J. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: Intracranial hemodynamics are important for management of SOAD. This study aimed to monitor peri-stent placement intracranial CirT of patients with SOAD. MATERIALS AND METHODS: Twenty-five patients received stent placement for extracranial ICA stenosis, and 34 patients with normal CirT were recruited as controls. Their color-coded DSAs were used to define the Tmax of selected intravascular ROI. A total of 20 ROIs of the ICA, OphA, ACA, MCA, FV, PV, OV, SSS, SS, IJV, and MCV were selected. rTmax was defined as the Tmax at the selected region of interest minus Tmax at the cervical segment of the ICA (I1 on AP view and IA on lateral view). rTmax of the PV was defined as intracranial CirT. Intergroup and intragroup longitudinal comparisons of rTmax were performed. RESULTS: rTmax values of the normal cohorts were as follows: ICA-AP, 0.12; ICA-LAT, 0.10; A1, 0.28; A2, 0.53; A3, 0.81; M1, 0.40; M2, 0.80; M3, 0.95; OphA, 0.35; FV, 4.83; PV, 5.11; OV, 5.17; SSS, 6.16; SS, 6.51; IJV, 6.81; and MCV, 3.86 seconds. Before stent placement, the rTmax values of arterial ROIs, except A3 and M3, were prolonged compared with values from control subjects (P < .05). None of the rTmax of any venous ROIs in the stenotic group was prolonged with significance. After stent placement, the rTmax of all arterial ROIs shortened significantly, except A1and M3. Poststenting rTmax was not different from the control group. CONCLUSIONS: Without extra contrast medium and radiation dosages, color-coded quantitative DSA enables real-time monitoring of peri-therapeutic intracranial CirT in patients with SOAD .